Evaluasi Pendidikan: Antara Konsep, Urgensi dan Efektivitasnya dalam Meningkatkan Mutu Pendidikan - Mohamad Toha; Munirah Munirah; Siti Mulkiyah (Multidisciplinary: Journal of Education an Learning, 2026)
Educational evaluation is a systematic process of collecting, analyzing, and interpreting information to assess the achievement of educational goals and improve the learning process and management of educational units. This article examines the concept of educational evaluation, its urgency in quality governance, and its effectiveness in driving improvements in educational quality. The discussion emphasizes the differences between evaluation and measurement and assessment, the various approaches (formative–summative, internal–external), and the requirements for evaluation to have a real impact: improvement-oriented, based on valid data, stakeholder involvement, and planned follow-up. The article also examines implementation challenges such as bias, achievement reductionism, administrative burden, and a "just report" culture. In conclusion, evaluation is effective when positioned as an organizational learning instrument that guides decisions, not merely an accountability ritual.